Penggunaan Aplikasi Chinese Conversation dalam Pembelajaran Percakapan bahasa Mandarin siswa Semester 4 Prodi Bahasa Mandarin UKI - Elyana, elyana (Fenghuang: Jurnal Pendidikan Bahasa Mandarin, 2023)
Learning Mandarin has been made easier by taking advantage of current technological developments, because there are many ways on how we can learn Mandarin by using a communication tool, in which almost all citizens in the world use a device called a mobile phone. So only with the internet and cellphone capital can we start learning language. Therefore, there are lots of applications that can make it easier to learn Mandarin without having to leave the house, one of the applications that will be discussed is the Chinese Conversation application. With this research helping students learn conversational Mandarin, it also explains the importance of conversation in learning Mandarin. In the research mmethod carried out steps such as research design, and data collection techniques with questionnaires to students. And the results of the study are that by using the Chinese Conversation application students can be made easier with the advantages that exist in the application features, and make students interested because there are fun words and pictures in learning Mandarin.